Retrospective multidisciplinary analysis of human alveolar echinococcosis in Hungary using spatial epidemiology approaches - Eszter Csulak; Ágnes Csivincsik; Tamás Sréter; Norbert Solymosi; József Danka; Zsolt Káposztás; Gábor Nagy; Balázs Dezsényi (Scientific Reports)
Abstract Human alveolar echinococcosis (HAE), which is caused by the larval stage of the Echinococcus multilocularis tapeworm, is an increasing healthcare issue in Hungary. Among the 40 known cases in the country, 25 were detected in the last five years. Our study aimed to reveal the geographically underlying risk factors associated potentially with these cases. We investigated the spatial pattern and the impact of potential risk factors of HAE by cluster analysis, and local and global regression models. Also, a questionnaire survey on the patients’ lifestyle was implemented. We found two HAE hyperendemic foci in the country with very dissimilar biotic and climatic features, and controversial impact of different environmental factors. Four factors, viz. forest cover (β = 0.291, p < 0.0001), surface soil wetness (β = − 0.157, p = 0.033), fox infection rate (β = 0.369, p < 0.0001) and socio-economic development (β = − 0.216, p = 0.009), proved important countrywide. The most forested and the least developed districts showed the highest HAE risk. Among the patients, kitchen gardening (67.86%) and dog ownership (67.86%) seemed the riskiest activities. Our models detected an anomaly in one of the poorest regions of Hungary where all risk factors behaved contrary to that of the neighboring areas. This phenomenon was supposed to be the result of under-detection of the disease, and it called attention to the urgent priority of knowledge dissemination to the public and the healthcare professionals.